Using urban facilities management principles to promote sustainable water management in informal settlements in South Africa - Ngobeni, Lulama (Department of Construction Economics and Management, 2025)
This research investigates the potential of Urban Facilities Management (UFM) in the promotion of sustainable water management practices in informal settlements in South Africa. The rationale for the study is that with the rapid increase in urban populations and the number of people living in informal settlements, there is an increased need for the adoption of sustainable water management. Guidance is required to implement Water Sensitive Design (WSD) approaches related to drainage and greywater management in informal settlements. The study adopted a mixed-methods approach. Key findings from the mixed-methods approach and UFM theoretical perspectives were used to develop a conceptual UFM-based framework for sustainable water management in informal settlements. The quantitative phase of the study made use of a Contingent Valuation based household survey to investigate Hout Bay residents' willingness to pay (WTP) for the provision of sustainable drainage systems (SuDS) and greywater management infrastructure in the neighbouring informal settlement of Imizamo Yethu situated upstream of Hout Bay, Cape Town. Findings reveal that the WTP for once-off payments was R408, and R71 for once-off payments over 12 months. Cumulatively, the household WTP contributed an aggregate total value (TWTP) of R3 200 700 of potential revenue for the implementation of WSD infrastructure in Imizamo Yethu. The respondents' attitudes and perceptions towards water and sanitation service delivery, and their interactions with the Disa River estuary were ranked using their Relative Importance Index (RII). The ranking indicated that the provision and facilitation of safe access to water and sanitation to all citizens, protection of freshwater systems, improving solid waste removal and the rehabilitation and restoration of freshwater systems were ranked first, second, third and fourth respectively. Furthermore, a linear regression analysis was conducted to examine the correlation between WTP and various independent variables including gender, income, age, employment status, satisfaction with the provision and maintenance of effective stormwater drainage in informal settlements and the rating of the importance of the rehabilitation and restoration of freshwater systems. The findings from the regression analysis revealed that the most significant (p = 0.0209) influence on the Willingness to Pay is the safety aspects related to the estuary. This research adopted the qualitative approach of interviewing stakeholders with experience in or knowledge about stormwater management projects in informal settlements was adopted. Eight semi-structured interviews were conducted. The qualitative data collected was analysed using the Reflexive Thematic Analysis approach (Reflexive TA). A total of five themes emerged from the Reflexive TA process. The results derived from the qualitative interviews and the subsequent themes that emerged, revealed the complexity of informal settlements, challenges associated with stormwater service delivery in informal settlements, key stakeholders in stormwater management projects, SuDS practices and processes, and the institutional knowledge and skill requirements for stormwater projects. The study contributes to knowledge of urban water service delivery and the implementation of WSD in informal settlements. Although UFM is acknowledged as having the potential to integrate people, places, processes and technology for the purpose of attaining sustainable urban environments, its applicability in the urban water management context has not been explored. The UFM-based framework developed from the study describes the focus areas that will assist with the implementation of WSD projects in informal settlements and gives insight into the factors that should be prioritised. The components of the framework include people (i.e., key stakeholders in projects), planning and design, products (the infrastructure and/or services), finances, maintenance and management, and processes that were identified as key components for the successful implementation of WSD projects. The study recommends that the framework be adopted in WSD projects, ensuring that the application thereof is context- specific to promote the overall development and liveability of informal settlements in South Africa.